How Community Nurses Manage Ethical Conflicts: A Grounded Theory Study. (December 2019) - Porr, Caroline; Gaudine, Alice; Woo, Kevin; Smith-Young, Joanne; Green, Candace
Research is limited on how nurses in community settings manage ethical conflicts. To address this gap, we conducted a study to uncover the process of behaviors enacted by community nurses when experiencing ethical conflicts. Guided by Glaserian grounded theory, we developed a theoretical model (Moral Compassing) that enables us to explain the process how 24 community nurses managed challenging ethical situations. We discovered that the main concern with which nurses wrestle is moral uncertainty ("Should I be addressing what I think is a moral problem?"). Moral Compassing comprises processes that resolve this main concern by providing community nurses with the means to attain the moral agency necessary to decide to act or to decide not to act. The processes are undergoing a visceral reaction, self-talk, seeking validation, and mobilizing support for action or inaction . We also discovered that community nurses may experience continuing distress that we labeled moral residue .